Perceptions of branding in the clothing industry - Andrissa van Eck; Anské Grobler; Frederick Herbst (Communicare)
Young Black adolescents can no longer be ignored as an important and strategic market segment in the South African clothing industry. Yet, very little research has been undertaken in the academic domain on their perceptions and attitudes on fashion in general and certain clothing items in particular. Psychological aspects influencing the buying behaviour of young male and female Black consumers have not been explored in great depth. The focus of this article was young Black consumers’ perceptions of branded versus unbranded clothes. The results of this exploratory study indicated that (i) both male and female Black adolescents share positive perceptions towards branded clothes; (ii) although unbranded items were perceived as less favourable, their worth was not denied; and (iii) when it comes to possible differences in the two genders’ perceptions of designer labels versus non-designer labels, they speak with one voice: designer labels are much preferred. The article concludes with recommendations to marketers in the South African clothing industry as well as some comments on future research on this increasingly important topic.